Evaluating E-Government Adoption in Rural Digital Transformation: A UTAUT Model Application in Indonesian Smart Village Initiative - Yuhefizar; Raemon Syaljumairi; Ervan Asri; Roni Putra (Ikatan Ahli Informatika Indonesia, 2024)
This research examines the implementation of electronic-based government systems (SPBE) in Nagari Batipuah Ateh, West Sumatra, Indonesia, analyzing the adoption patterns and challenges of digital transformation in rural governance. Through the application of the Unified Theory of Acceptance and Use of Technology (UTAUT) model, this study investigates how traditional rural communities adapt to and accept e-government services while maintaining their cultural identity and social structures. The study employed a mixed-method approach, combining quantitative surveys of fifty participants with qualitative insights from fifteen in-depth stakeholder interviews conducted over twelve months. The research focused on measuring key UTAUT constructs: performance expectancy, effort expectancy, social influence, and facilitating conditions, while also examining the role of community dynamics in technology adoption. Findings reveal significant correlations between social influence and behavioral intention (r = 0.72), highlighting the crucial role of community leadership in technology acceptance. While 52% of users demonstrated advanced digital literacy, 26% required substantial support for basic system navigation, leading to the emergence of effective community-based support networks. The study identified a 65% increase in adoption rates among initially hesitant users through these informal support systems, and a 58% higher sustained engagement when implementing phased approaches with community feedback integration. The research contributes to understanding rural digital transformation by demonstrating how e-government services can be successfully implemented while preserving cultural integrity. The results suggest that successful rural digital governance requires more than technological solutions, demanding careful attention to social dynamics and cultural contexts.